Information technologies and mathematical modelling : queueing theory and applications : 17th International Conference, ITMM 2018, named after A.F. Terpugov, and 12th Workshop on Retrial Queues and Related Topics, WRQ 2018, Tomsk, Russia, September 10-15, 2018, Selected papers /: queueing theory and applications : 17th International Conference, ITMM 2018, named after A.F. Terpugov, and 12th Workshop on Retrial Queues and Related Topics, WRQ 2018, Tomsk, Russia, September 10-15, 2018, Selected papers. (2018) - Unknown
No abstract available